The Katyń Families: A Polish Lesson in Contemporary History. (November 2015) - Sariusz-Skąpska, Izabella
By appearance it would seem that Rodziny Katyńskie—the Katyń Families—are a veterans' organization. The elderly, the last witnesses of the terrible Second World War, make up the majority of members. But these are not heroes, and they are not veterans. Who are they? In the first days after Poland regained its independence, after the first free elections of 4 June 1989, people from many cities leave the quiet of their homes and for the first time in their lives start talking about the history of their fathers, who had gone missing after 17 September 1939. The Katyń Families were formed. Statutes were written, and the aims of the organization were defined: explaining all of the circumstances of the Katyń Massacres, finding all of the locations where Polish prisoners of war died, and, finally, accomplishing their dignified burial in Polish War Cemeteries.